Enhanced liver fibrosis score as a noninvasive biomarker in hepatitis C virus patients after direct-acting antiviral agents - Cossiga, Valentina; La Civita, Evelina; Bruzzese, Dario; Guarino, Maria; Fiorentino, Andrea; Sorrentino, Rosanna; Pontillo, Giuseppina; Vallefuoco, Luca; Brusa, Stefano; Montella, Emma; Terracciano, Daniela; Morisco, Filomena; et al. (Frontiers in Pharmacology, 2022)
Background: In more than 90% of chronic viral hepatitis C (HCV) patients treated with direct-acting antiviral agents (DAAs), a sustained viral response (SVR) was observed. Unfortunately, there are subgroups of subjects who display enduring liver fibrosis and are at high risk of developing hepatocellular carcinoma (HCC). Thus, liver fibrosis evaluation during the follow-up of these patients plays a pivotal role. The gold standard to evaluate hepatic fibrosis is liver biopsy, which is an invasive procedure. Imaging techniques and serum biomarkers have been proposed as safer and cheaper procedures. Objectives: In this study, we evaluated the concordance of transient elastography (TE) with ELF score ( enhanced liver fibrosis) in a cohort of patients with HCV before and after direct-acting antiviral (DAAs) treatment. ELF score has been validated in other chronic liver diseases; the evidence is not available in HCV patients treated with DAAs. Study design: We prospectively recruited all consecutive HCV patient candidates for DAAs therapy at the University of Naples “Federico II” between April 2015 and July 2016. TE and ELF scores were assessed at baseline, at SVR24, and at SVR48. Results: One-hundred-nineteen patients were treated with DAAs, and 94.1% of them reached SVR. A total of 55.5% of patients were males with a mean age of 64.7 ± 9.6 years. TE results revealed that 12 patients (10%) had F1-2 mild/moderate fibrosis, and 107 (90%) had F3-4 advanced fibrosis. At baseline, SVR24, and SVR48, the concordance between ELF test and TE was poor: 0.11 (p = 0.086), 0.15 (p = 0.124), and 0.034 (p = 0.002), respectively. However, at SVR24 and SVR48, both methods showed a significant amelioration of liver fibrosis compared to baseline (p < 0.001). In addition, both ELF index and TE were significantly associated with portal hypertension at baseline, but not with varices and ascites. Conclusions: Our findings suggested that ELF test could predict changes in liver fibrosis, independently of TE. In case of TE unavailability, ELF score could represent an appropriate tool. Notably, in the context of the COVID-19 pandemic, ELF testing should be encouraged to reduce unnecessary access to the hospital and prolonged physical contact.